2010
DOI: 10.1002/pmic.200900783
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for comprehensive identification of human N‐myristoylated proteins using an insect cell‐free protein synthesis system

Abstract: To establish a strategy for the comprehensive identification of human N-myristoylated proteins, the susceptibility of human cDNA clones to protein N-myristoylation was evaluated by metabolic labeling and MS analyses of proteins expressed in an insect cell-free protein synthesis system. One-hundred-and-forty-one cDNA clones with N-terminal Met-Gly motifs were selected as potential candidates from approximately 2000 Kazusa ORFeome project human cDNA clones, and their susceptibility to protein N-myristoylation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…0 -GCATGCGATCGCCAT-GGGCAACCTGGAGAGCGCC-3 0 and FXC1701-PmeI C, 5 0 -ATAT-GTTTAAACCGTGGGGGCCTGGAGT-3 0 , as primers, with pcDNA3-FXC1701-FLAG 11) as template. Plasmid pcDNA3-EGFP, containing the cDNA coding for EGFP, was constructed by PCR using two oligonucleotides, EcoRV-EGFP N, 5…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…0 -GCATGCGATCGCCAT-GGGCAACCTGGAGAGCGCC-3 0 and FXC1701-PmeI C, 5 0 -ATAT-GTTTAAACCGTGGGGGCCTGGAGT-3 0 , as primers, with pcDNA3-FXC1701-FLAG 11) as template. Plasmid pcDNA3-EGFP, containing the cDNA coding for EGFP, was constructed by PCR using two oligonucleotides, EcoRV-EGFP N, 5…”
Section: Methodsmentioning
confidence: 99%
“…0 -ATATGCGA-TCGCGATGGCAAACGCAGGGAGCATG-3 0 and FM2-Ástop-PmeI C, 5 0 -GCGCGTTTAAACCATTGTTATTTCGGC-3 0 , as primers, pcDNA3-FXC1184 11) as template. After digestion with SgfI and PmeI, the amplified fragments were subcloned into the SgfI-EcoRV sites of pcDNA3-FL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that in vitro translation of complementary DNA (cDNA) coding for N-myristoylated protein in the presence of [ 3 H] myristic acid followed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and fluorography is a useful method for the detection of protein N-myristoylation [18][19][20]. However, this strategy, like other approaches, is still in need of improvement.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, the heterogenicity of the lipid groups present in the GAP-43 protein, which has two acylated cysteines near the C-terminus, was studied by MALDI-TOF and confirmed by Quadropole-TOF MS/MS indicating that not only palmitoyl but also stearic acid can be attached on these cysteines [51]. Recently, MALDI-MS was also used for the detection of purified myristoylated and isoprenylated proteins generated in an insect-cell free protein synthesis system [88][89][90]. However, one of the limitations of this approach is the high hydrophobicity of the lipidated samples, which usually results in low efficiency of peptide recovery during sample preparation as well as peptide detection.…”
Section: Mass Spectrometrymentioning
confidence: 99%